More Than a COVID-19 Response: Sustaining Mutual Aid Groups During and Beyond the Pandemic - Fernandes-Jesus, Maria; Mao, Guanlan; Ntontis, Evangelos; Cocking, Chris; McTague, Michael; Schwarz, Anna; Semlyen, Joanna; Drury, John (Frontiers in Psychology, 2021)
Mutual aid groups have been an indispensable part of the public response to the COVID-19 pandemic. They have provided many forms of support, in particular grocery shopping which has enabled people to self-isolate if required. While community solidarity during emergencies and disasters is common, previous studies have shown that such solidarity behaviours tend to decline over time, even when needs remain high. In this study, we address how mutual aid groups can be sustained over time in the context of the COVID-19 pandemic. We conducted 32 interviews with organisers of COVID-19 mutual aid and community support groups in the UK between September 2020 and January 2021. Based on a reflexive thematic analysis, we identified several community and group level experiences and strategies that were related to sustained participation in COVID-19 mutual aid groups. Meeting community needs over time with localised action and resources and building trust and community-based alliances were foundational elements in the COVID-19 mutual aid groups. Group processes strategies, such as a culture of care and support and regular group meetings, were used to help to sustain involvement. Some experiences resulting from participation in COVID-19 mutual aid groups were also related to sustained participation, including positive emotions (e.g., joy, pride), well-being and sense of efficacy, and an increasing sense of local community belonging and cohesion. Based on these findings, we propose four practical recommendations for sustaining mutual aid groups to assist public engagement with protective behaviours in the COVID-19 pandemic and beyond. We recommend providing practical and financial support to COVID-19 mutual aid groups; to mobilise the knowledge and the experiences acquired by COVID-19 mutual aid groups for developing programmes and interventions for addressing the medium and long-term impacts of COVID-19; to prioritise community-level interventions; and to recognise the role of group processes as these have the potential to lead to long-term community responses. These approaches will be key for ensuring that communities effectively recover from the COVID-19 pandemic.